Negative impacts of chalets operation on the peninsular Malaysia marine park islands - Yusof, Zeenat Begam; Zakariya, Khalilah; Che Haron, Roziha; Sapian, Abdul Razak; Asif, Nayeem; Haraty, Hayder Jawad Shakir (International Publishing House, Ltd., 2021)
The popularity of marine tourism put intense pressure on the island's environment. Limited studies were conducted to determine the negative impacts caused by chalets operation. Study aim is to investigate the adverse effects caused by the chalet’s operation on the Tioman and Perhentian Island. The objectives are to identify operation activities and the negative impact caused by the operation. The study was conducted by adopting qualitative method. The findings indicate solid waste disposal, groundwater extraction, and sewage disposal are destroying the marine environment in many ways. Several recommendations were provided to reduce the negative impacts.